2008
DOI: 10.1002/jez.b.21214
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP concentration and protein kinase A (PKA) gene expression at different developmental stages of the polychaete Hydroides elegans

Abstract: The phosphodiesterase inhibitor 3-isobutyl-1-methylxanthine (IBMX) showed inductive effect on larval settlement of the polychaete Hydroides elegans. It has been suggested that IBMX triggers larval settlement by elevating the cellular adenosine 3',5'-cyclic monophosphate (cAMP) level in this species. To test this hypothesis, we first examined cAMP-level changes in both the competent (CL) and attached larvae (AL) and then characterized the cAMP-dependent protein kinase in H. elegans, which is the major mediator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…Three of the four proteins concerned with ATP synthesis were down-regulated by BPA while all of them were down-regulated by NPs, indicating the inhibition of these EDCs on ATP synthesis. ATP not only provides energy for embryogenesis but also served as the substrate for adenylate cyclase in the formation of the second messenger cyclic adenosine monophosphate, which induces the metamorphosis of invertebrates (Clare et al 1995;Li et al 2008;Morse 1990). Therefore, inhibition of ATP synthesis would directly lead to the failure of metamorphosis.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the four proteins concerned with ATP synthesis were down-regulated by BPA while all of them were down-regulated by NPs, indicating the inhibition of these EDCs on ATP synthesis. ATP not only provides energy for embryogenesis but also served as the substrate for adenylate cyclase in the formation of the second messenger cyclic adenosine monophosphate, which induces the metamorphosis of invertebrates (Clare et al 1995;Li et al 2008;Morse 1990). Therefore, inhibition of ATP synthesis would directly lead to the failure of metamorphosis.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the present study yields the first outcomes on the effect of IBMX on larval settlement of M. galloprovincialis. Our results revealed that both settlement and mortality were enhanced with an increasing dose of IBMX, with peak values of 79.2 and 40.5%, respectively, at 10 − 3 M. It has been suggested that IBMX enhances intracellular levels of the secondary messenger 3′,5′-cyclic adenosine monophosphate (cAMP) by inhibiting phosphodiesterases, the enzymes causing the cAMP degradation, which in turn would trigger the response of cAMP pathway, with a probable intervention of a protein kinase A ( Bryan et al, 1997;Dobretsov and Qian, 2003;Li et al, 2008 ;Pechenik and Qian, 1998). However, the relationship between the elevated intracellular cAMP levels and larval settlement and metamorphosis response needs to be far further examined.…”
Section: Discussionmentioning
confidence: 99%
“…This molecular character also corresponds across all arthropod groups and lophotrochozoan phyla including annelids, Platyhelminthes and nemerteans [3]. Because Drosophila protein DC0 and mammalian PKA-Ca are 82% conserved [57], and because the sequence of protein kinase A is highly conserved across Metazoa [58,59], immunohistological localization of this enzyme should allow the detection of possible corresponding centres even across very distantly related phyla. Additionally, antibodies against phosphorylated Ca 2þ /calmodulin-dependent protein kinase II (pCaMKII) likewise localize to centres that correspond to the insect mushroom body across Ecdysozoa and Lophotrochozoa, show highly conserved sequence between insects and mammals, and may also reveal structures that correspond genealogically across the Bilateria [3,60].…”
Section: Introductionmentioning
confidence: 86%